The Design of Media on Two-Lens System Experiment (MTLSE) for Pre-service Physics Teachers - Saprudin Saprudin; Liliasari Liliasari; Ary Setijadi Prihatmanto; Andhy Setiawan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
This article is a part of the research in designing a model of the geometrical-optics game on optics' courses for pre-service physics teachers (PPTs). This article describes the preliminary form of product, the result of validation, and PPTs’ responses to the media on two-lens system experiment (MTLSE). The validation of this media has been done according to physics subject matter, instructional media and pedagogical experts. The implementation of MTLSE using the one-shot case study design involving 25 PPTs at one of the Islamic universities in Bandung. We collected the data of MTLSE validation and PPTs’ responses through non-test techniques with questionnaire instruments. The data using quantitative descriptive analysis technique. The results of MTLSE validation can be good categorized. Besides, generally, the PPTs’ responses are good categorized toward the implementation of MTLSE on optics' courses.